Synthesis, Infrared Spectroscopy and Crystal Structure Determination of a New Decavanadate - Guilherme, Luciana Rebelo [UNESP]; Massabni, Antonio Carlos [UNESP]; Dametto, Alessandra Cristina [UNESP]; Correa, Rodrigo de Souza; de Araujo, Alexandre Suman (Springer/plenum Publishers, 2010)
Synthesis, infrared spectroscopy and crystal structure of a new potassium decavanadate decahydrate, K-6[V10O28] 10H(2)O, has been reported The infrared spectrum is dominated by decavanadate polyanion and water bands The X-ray crystallography analysis found the compound crystallizes in a triclinic system with the parameters a = 10 5334 (4) angstrom, b = 10 6600 (4) angstrom, c = 17 7351 (5) angstrom, alpha = 76 940 (2)degrees, beta = 75 836 (2)degrees, gamma = 64 776 (2)degrees, V = 1,729 86 (11) A(3), Z = 2, space group P (1) over bar The polyanion consists of ten [VO6] octahedra sharing edges, in which the V-O distances are in good agreement with those reported for other decavanadates The crystal structure is stabilized by potassium cations and water molecules forming a complex pattern of hydrogen bonding and short contact ionic interactions
Keywords: Potassium decavanadate decahydrate; Infrared spectrum; Crystal structure; Molecular interaction